1990
DOI: 10.1002/aic.690361103
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Carbon Dioxide with tertiary Amines in aqueous solution

Abstract: The reaction of CO, with TEA, DMMEA, and DEMEA has been studied at 293, 303, 318 and 333 K. All the kinetic experiments were carried out in a stirred cell reactor operated with a flat, smooth and horizontal gas-liquid interface. A numerical method, which describes mass transfer accompanied by reversible chemical reactions, has been applied to infer rate constants from the experimental data. It is argued that the contribution of the CO, reaction with OH-to the observed reaction rate may have been overestimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
156
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(177 citation statements)
references
References 27 publications
19
156
2
Order By: Relevance
“…Physical absorption experiments in aqueous solutions have been presented by Versteeg et al (1987) for the stirred cell reactor applied in the kinetic experiments reported by Blauwhoff et al (1984), Versteeg and van Swaaij (1988a, b), Bosch et al (1990) and Littel et al (1990). Versteeg et al (1987) reported a Sh, SC, Re relationship and observed that the stirrer position relative to the gas-liquid interface did not affect the mass transfer coefficients.…”
Section: Many Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical absorption experiments in aqueous solutions have been presented by Versteeg et al (1987) for the stirred cell reactor applied in the kinetic experiments reported by Blauwhoff et al (1984), Versteeg and van Swaaij (1988a, b), Bosch et al (1990) and Littel et al (1990). Versteeg et al (1987) reported a Sh, SC, Re relationship and observed that the stirrer position relative to the gas-liquid interface did not affect the mass transfer coefficients.…”
Section: Many Authorsmentioning
confidence: 99%
“…Sharma, 1965: BlauwholT et al, 1984Sada et al, 1985Sada et al, , 1986Haimour et al, 1987;Versteeg and van Swaaij, 1988a;Littel et al, 1990). Deduction of kinetic rate constants from gas absorption experiments can be very complex as a lot of interacting phenomena are involved.…”
Section: Many Authorsmentioning
confidence: 99%
“…The kinetics of the reaction of CO 2 with aqueous MDEA was widely investigated [12,15,21,[24][25][26][27][28][29] using several experimental techniques. Although the kinetic mechanisms for tertiary amines are much simpler than for primary or secondary amines, for which carbamate formation has to be considered, discrepancies have appeared in the literature concerning the reported rate constants which are summarized in Table 2.…”
Section: Example Of Analyzing the Absorption Experiments -Reaction Ofmentioning
confidence: 99%
“…It can also be used in gas-liquid-solid reactions, where the solid is a reactant. A considerable amount of kinetic studies is available in the literature with the use of this apparatus [3,[11][12][13][14][15].…”
Section: Heterogeneous Techniquesmentioning
confidence: 99%
“…This technique has been widely applied to determine reaction rate constants involved in chlorine hydrolysis, H 2 S absorption in chlorine solution, flue desulfurization, NOx absorption or CO 2 capture in amine solutions. [5][6][7][8][9][10][11][12][13][14][15][16] Most of time, reactive absorption is applied using (i) batch reactors in which the gas and liquid phases are separated by a flat interface (stirred-cell reactor). The absorption rate, and consecutively the reaction rate, are deduced 4 pressure at the contactor outlet was nearly identical to the inlet one, and only the reactant concentration decay over time was recorded to determine the mass-transfer and chemical reaction rates.…”
Section: Introductionmentioning
confidence: 99%